2012
DOI: 10.1038/ki.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 plays a profibrotic and pro-inflammatory role during ureteric obstruction

Abstract: Thrombospondin-1 (TSP-1) is an endogenous activator of transforming growth factor-β (TGF-β), and an anti-angiogenic factor, which may prevent kidney repair. Here we investigated whether TSP-1 is involved in the development of chronic kidney disease using rats with unilateral ureteral obstruction, a well-known model to study renal fibrosis. Obstruction of 10 days duration induced inflammation, tubular cell atrophy, dilation, apoptosis, and proliferation, leading to interstitial fibrosis. TSP-1 expression was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 51 publications
5
39
1
7
Order By: Relevance
“…по многим функциям противоположен VEGF [7,8,17]. Взаимодействуя с трансформирующим β-фактором роста (TGF-β), THBS1 регулирует клеточно-матриксные взаимодействия и оказывает профиброгенное действие [18,19].…”
Section: Discussionunclassified
“…по многим функциям противоположен VEGF [7,8,17]. Взаимодействуя с трансформирующим β-фактором роста (TGF-β), THBS1 регулирует клеточно-матриксные взаимодействия и оказывает профиброгенное действие [18,19].…”
Section: Discussionunclassified
“…The authors treated primary isolated mesangial cells with leptin and showed that leptin-stimulated ECM production was abolished by TSP1 deficiency (21). Moreover, TSP1 deficiency or treatment with shRNA against TSP1 was protective in mouse UUO, leading to decreased inflammation and fibrosis, increased VEGF expression and preserved endothelial capillary network (22,23). TSP1 was also found to mediate high-fat diet-induced skeletal muscle fibrosis or diabetes-induced myocardial fibrosis by either inducing collagen expression or inhibiting collagen degradation through regulation of MMP2 and MMP9 activities, respectively (24,25).…”
Section: Thrombospondinsmentioning
confidence: 99%
“…En conditions pathologiques, elle a été analysée in vivo dans différents modèles de néphropathies. Après ischémie-reperfusion [27], réduction néphronique [28], obstruction urétérale unilatérale [29], mais aussi au cours du vieillissement rénal [30], du diabète [31] et de nombreuses autres néphropathies glomérulaires expérimentales [32,33], les cellules épithéliales tubulaires expriment de novo la TSP-1. In vitro, l'hypoxie [34] et l'enrichissement du milieu de culture en glucose [31,35] [33].…”
Section: Expression De La Thrombospondine-1 Au Cours Des Néphropathieunclassified
“…Chez le rat, l'obstruction urétérale unilatérale induit une expression de novo de l'ARNm de tsp-1 et de la protéine TSP-1 par les tubules lésés. Cette expression est corrélée au contenu rénal en TGF-, et diminue parallèlement à celle du TGF- après désobstruction urétérale [29]. L'inhibition spécifique de l'activation du TGF- par la TSP-1 (via l'administration du peptide LSKL) a été étudiée dans trois modèles de néphropathie.…”
Section: Expression De La Thrombospondine-1 Au Cours Des Néphropathieunclassified
See 1 more Smart Citation